TRANSFORMASI DOKTRIN AL-MA'UN TERHADAP PENGUATAN GERAKAN EKONOMI MUHAMMADIYAH - Saefudin Saefudin (ITB AAS INDONESIA Surakarta, 2022)
The existence of Muhammadiyah as a tajdid movement began to be eroded by globalization due to the lack of understanding among Muhammadiyah followers was only in the implementation of mandatory. Whether we realize it or not, Muhammadiyah is now faced with a vortex of ideological struggle amidst the capitalism hegemony, liberalism, the welfare state, socialism, communism, fascism, and communities’ economy. This research aimed at discovering and analyzing the transformation of the doctrine on the strengthening of the economic movement as well as the Islamic economic perspective on it. This qualitative research with a library design. This study concluded that the doctrine was transformed into a massive thought concept for strengthening Muhammadiyah economic movement. The concept consisted of Muhammadiyah Incorporated and Strategic Partnership. These two transformations were basically focused on the empowerment and liberation of the mustadl'afin. On the perspective of Islamic economics, the strong interrelation could be seen from the philosophical values existing in justice and monotheism. These two values unite into one creating prosperity through the empowerment and liberation of the mustadl'afin. Keywords : Transformation, Al-Ma’un Doctrine and Mustadl’afin.